(untitled) (Research, Society and Development, 2020)
Kefir is a probiotic fermented milk that can have its functional appeal reinforced with the addition of prebiotic ingredients, such as inulin. The objective of the work was to evaluate the influence of the addition of inulin on the physical-chemical and sensory parameters of sweetened and flavored kefir formulations with green fruits, elaborated by two fermentative methods. Four kefir formulations were made: FS1 - Kefir with inulin, FS2 - Kefir without inulin (prepared with kefir grains), FS3 - Kefir with inulin, FS4 - Kefir without inulin (prepared with lyophilized starter culture). The addition of inulin did not influence the fermentation process of fermented milks, formulations FS1 and FS2 showed higher acidity and lower pH. All samples are in accordance with the legislation for protein and lipid content and the addition of inulin and green fruit preparation contributed to the increase in the solids content, reflecting in the moisture content, with an increase in the carbohydrate content and energy value. In the sensory analysis, all fermented milks had good acceptance, with scores above 6 for the texture attribute in formulations with the addition of inulin. This prebiotic also did not impart residual flavor and color change. Based on the results, it can be concluded that kefir made from lyophilized starter culture, added inulin and prepared from green fruits is a good option to meet the growing demand for functional foods in the market, with a greater standardization compared to formulations made with kefir grains.